Implementasi Digital Signature Pada Dokumen Elektronik Berbasis QR-Code - Gunawan, Rohmat; Rahmatulloh, Alam; Rizal, Randi (Universitas Indraprasta PGRI Jakarta, 2024)
Documents can now be sent not only in paper form, but also in electronic form, making the distribution process faster. However, documents that require signature validation must be printed and signed conventionally before being sent. This conventional process is time-consuming and cannot be completed if the signer is not present. Balai Sertifikasi Elektronik (BSrE) which is under the auspices of Badan Siber dan Sandi Negara (BSSN) has an information system that implements the digital signature concept. However, this concept is limited to state administration institutions and has a closed source code, preventing it from being developed by the public. The aim of this research is to apply a QR Code-based digital signature system for signing electronic documents. The research method consists of problem identification, system architecture design, implementation, and testing. Based on the results of experiment, digital signatures using cryptographic techniques and QR Codes have been successfully applied in the process of signing electronic documents. Thus, the document signing process can be carried out without printing it first. Each QR-Code successfully embedded in an electronic document as a digital signature can store metadata: date, subject, name of signatory, position, institution or unit. Verification can be performed to ensure that the data stored behind the QR-Code is associated with a document that has been affixed with a digital signature.